Pengaruh Media Pembelajaran Terhadap Hasil Belajar Siswa - Inayatullah, Putri Asti; Suprapto, Suprapto; Nadiah, Nadiah (Yayasan Pendidikan dan Pengembangan Harapan Ananda, 2024)
This study aims to examine the effect of the Kahoot learning media on student learning outcomes at SMK Pelita Tiga Jakarta. The use of Kahoot as a learning media was chosen due to its efficiency, innovativeness, and ability to help achieve learning objectives at a lower cost. The research method used is a quantitative approach with a correlation method. This study involved 24 students selected using the Cluster Sampling technique. Data collection was conducted through questionnaires and documentation, while data analysis was performed using the product moment correlation technique. Based on calculations, the product moment correlation value for 24 degrees of freedom (df) at a 5% significance level is 0.404, and at a 1% significance level is 0.515. The analysis results show that the observed correlation value (ro) of 0.617 is greater than the table value (rt) at both significance levels. Therefore, the null hypothesis is rejected, and the alternative hypothesis is accepted, indicating a positive effect of Kahoot learning media on student learning outcomes at SMK Pelita Tiga Jakarta. The implication of this study is that Kahoot can be an effective alternative learning media to improve student learning outcomes.